Regional Economic Integration and FDI in South Asia : Prospects and Problems - Aradhna Aggarwal (Indian Council for Research on International Economic Relations (ICRIER), 2008)
The slow progress and modest achievements of regional integration in South Asia have generated a huge amount of skepticism about its role as an effective strategy of growth. The present study, however, argues that there is need to forge deeper integration within the region. It examines the prospects and problems of serious fiscal consolidation within the area. Essentially, it looks at the effect of deepened regionalism on investment flows. It argues that regional integration has the potential to promote intra and extra regional FDI flows and economic development in individual countries of the region. This will pave the way for the most efficient use of the region's resources through additional economies of scale, value addition, employment and diffusion of technology. A number of challenges remain. Structural weaknesses, institutional bottlenecks, political movements, narrow nationalism and mutual mistrust are some of the factors that explain the failure of the region to exploit possibilities. Paradoxically, the problems themselves provide strong motivation for strengthening cooperation. It is only through more intensive collaboration that these complexities can be addressed and resolved.
Keywords: F15; F21; F23; 330; Regional integration; South Asia; intra regional FDI; extra regional FDI; SAFTA; Regionale Wirtschaftsintegration; Auslandsinvestition; Südasien; SAARC-Staaten